Political youth groups in a public university in Minas Gerais: micro-public space and experiences of participation in the student movement (Práxis Educativa, 2019)
This paper describes the configuration of a student public micro-space, based on the action of youth groups, at a Federal University in Minas Gerais, Brazil. The dynamics of three of these collectives are analyzed through field research between 2016 and 2018, with observations and semi-structured interviews. The emergence and evacuation of this micro-space were accompanied by the analysis of events of the student politics as well as a vigorous collective action of the university occupation in the second half of 2016. The results deal with the processes of engagement/disengagement and mobilization/demobilization during this cycle of youth protests in the 2010s, in a particular case, besides the difficulties of a new contingent of students, coming from the expansion of public Higher Education, to maintain their political participation. Keywords: Student movement. Militancy. Activism. Engagement.